Contributors to this edition - Ronit Frenkel (The Thinker)
The University of Johannesburg acquired The Thinker in April 2019 from Dr Essop Pahad. Over the last decade, The Thinker has gained a reputation as a journal that explores Pan-African issues across fields and times. Ronit Frenkel, as the incoming editor, plans on maintaining the pan-African scope of the journal while increasing its coverage into fields such as books, art, literature and popular cultures. The Thinker is a ‘hybrid’ journal, publishing both journalistic pieces with more academic articles and contributors can now opt to have their submissions peer reviewed. We welcome Africa-centred articles from diverse perspectives, in order to enrich both knowledge of the continent and of issues impacting the continent.